Review Essay: What Are We Struggling For? (Concept: The Journal of Contemporary Community Education Practice Theory, 2015)
review ofThe crucible of resistance:  Greece, the Eurozone & the world economic crisis.  Christos Laskos and Euclid Tsakalotos.  London:  Pluto Press.  2013. After neoliberalism?  The Kilburn manifesto.  Stuart Hall, Doreen Massey and Michael Rustin (eds.).  London:  Lawrence and Wishart Ltd.  2015.